2008
DOI: 10.1097/mca.0b013e32830eab8c
|View full text |Cite
|
Sign up to set email alerts
|

Serum gamma-glutamyl transferase activity: new high-risk criteria in acute coronary syndrome patients?

Abstract: In acute coronary syndromes (ACS), oxidation and inflammation have very important roles and in-vitro studies have demonstrated that gamma-glutamyl transferase (GGT) participates in such oxidative and inflammatory reactions. We aimed to evaluate the prognostic value of baseline serum GGT activity on the development of major adverse cardiac event (MACE) in the follow-up of the patients with ACS in coronary care unit (CCU), after 1 and 6 month periods. We included 117 patients (mean age: 61.2+/-11.3 years, 93 mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
36
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 16 publications
4
36
2
Order By: Relevance
“…Similarly, oxidative stress and inflammation modulate the NO system and lead to endothelial dysfunction (38). Serum GGT activity is associated with major cardiovascular events in acute coronary syndrome (39,40). In addition, a significant correlation was demonstrated between serum GGT levels and coronary artery calcification and coronary complexity in stable CAD (41,42).…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, oxidative stress and inflammation modulate the NO system and lead to endothelial dysfunction (38). Serum GGT activity is associated with major cardiovascular events in acute coronary syndrome (39,40). In addition, a significant correlation was demonstrated between serum GGT levels and coronary artery calcification and coronary complexity in stable CAD (41,42).…”
Section: Discussionmentioning
confidence: 97%
“…other known CAD risk factors as well as alcohol consumption (1)(2)(3)(24)(25)(26)(27). Also in patients with stable CAD, serum GGT was associated with prognosis independent of a variety of established risk markers (28).…”
Section: Discussionmentioning
confidence: 97%
“…The patients were evaluated according to their background features such as DM, HT, CAD and previously used medications ( Table-III 25) and median GGT level of alive patients was 22.00 (15.00-35.00). GGT level of dead patients was significantly higher compared to GGT levels of alive patients (p=0.048).…”
Section: Resultsmentioning
confidence: 99%
“…14 Ulus et al assessed GGT activity and major adverse cardiac event (mortality from cardiac causes, recurrent hospitalization with ACS and nonfatal recurrent MI diagnosis, to need for coronary revascularization during in Coronary Care Unit (CCU)) patients due to acute coronary syndrome for 1-6 months period. 25 They showed that increased GGT activity, even in normal limits, is an independent prognostic factor for adverse cardiac event development in relatively high risk ACS patients. According to our results, high GGT levels are correlated with early mortality in stroke independently of alcohol consumption.…”
mentioning
confidence: 99%